Comparative Analysis Language Style in English and Sangihe Siau Dialect - Riahi, Sri; Hampp, Paula; Kumayas, Tirza A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study uses descriptive and contrastive analysis. Data in English were collected from books related to sociolinguistics, speaking books, and sources from the internet. Data in Sangihe language were collected by writing and recording conversations in situations, times, and opportunities such as conversations that occur when passing each other. On the street, conversations between family members (at home), conversations between teachers and school officials, conversations in the office, places of worship, and others, the data were analyzed using the concepts of Fishman, Tillit, and Bruder and to explore language comparisons using comparative theory. The results of the study indicate that the comparison Language style between English and Sangihe dialect Siau in forms and patterns in greetings and expressions farewell in has two forms, namely formal and informal. In addition, researchers found three patterns in greetings in English and Siau language. Sangihe dialect. The patterns are formal greetings, informal greetings, and not greeting each other. The pattern is the same in English, namely saying goodbye as a greeting. Meanwhile, the Sangihe language dialect Siau only has two greeting patterns, namely formal and informal. S alam and expressions farewell in English and Sangihe is different. For example, greetings and farewells in English are diverse. Meanwhile, in Sangihe, they are limited.